Self-harm and suicide attempts among incarcerated lesbian, gay and bisexual people in Australia. (April 2023) - Hail-Jares, Katie; Cumming, Craig; Young, Jesse T; Borschmann, Rohan; Lennox, Nick; Kinner, Stuart A.
Objectives: Guided by minority stress theory, we explored the association between sexual identity, justice system involvement, self-harm and suicide attempts, among a cohort of incarcerated adults in Australia. Methods: A sample of 2698 adults incarcerated in Queensland and Western Australia were surveyed between 1 August 2008 and 12 August 2016 about their current psychological distress, mental health diagnoses, contact with mental health services, and lifetime and recent self-harm and suicide attempts. We used multivariable logistic regression to explore the relationship between sexual orientation, prior criminal justice system involvement, mental health and demographic factors. Results: Five percent of the sample identified as gay, lesbian or bisexual, with 37% of lesbian, gay, bisexual and other same-sex attracted individuals reporting that they had self-harmed (vs 14% of heterosexual peers; χ 2 = 52.4; p < 0.001) and 49% reporting a history of at least one suicide attempt (vs 23%; χ 2 = 49.2; p < 0.001). Lesbian, gay, bisexual and other same-sex attracted people were 2.1 times (95% confidence interval: [1.4, 3.3]) and 1.8 times (95% confidence interval: [1.2, 2.8]) more likely to report a history of self-harm and suicide attempt, respectively, than non–lesbian, gay, bisexual and other same-sex attracted respondents. Conclusion: Intersectionality theory suggests that people who are navigating two or more marginalised identities often experience a compounding of internal and external stressors. Consistent with that theory, lesbian, gay, bisexual and other same-sex attracted people who experience incarceration may be at particularly high risk of self-harm and suicidal behaviour. Custodial settings should both improve cultural competency for frontline staff working with lesbian, gay, bisexual and other same-sex attracted individuals and improve access to mental health services during incarceration.